KOMPARATIF HASIL BELAJAR IPS MODEL PEMBELAJARAN KOOPERATIF DENGAN MEMPERHATIKAN KEMAMPUAN MENGELOLA EMOSIONAL - Siswati Handayani; Darsono Darsono; Tedi Rusman (Jurnal Studi Sosial / Journal of Social Studies, 2013)
This research aimed at finding out;1).Interaction between models of cooperative learning, the ability to manage emotional and learning result,2) Differences learning result the model of TGT and TAI,3) Differences learning result that have the ability to manage high progess and low emotional,4)Differences learning result are model TGT and TAI who have the ability to manage the high emotional,5)Difference in learning result model TGT and TAI who have the ability to manage low emotional. Based on data analysis results are;1).There was interaction between models of cooperative learning, the ability to manage emotional and learning result,2).There is difference of TGT and TAI learning result of ability to manage emotional high and low ability students manage emotional,3)There is differences between ability to manage the high emotional and low emotional of learning result that used both TGT and TAI,4).There is a differences in average learning result TGT and TAI model who have the ability to manage emotional,5).There is a differences in average learning result TGT and TAI model who have the ability to manage emotional,6)which model is more effective between the TGT and for the subject of social studiesKeywords:  cooperative learning model , the ability of student’s emotional management, learning result